The Influence of Using Social Media on Students' Motivation and Learning Achievement in Economics Subjects at Daarun Nahdhah Thawalib Bangkinang Islamic Boarding School - Fudhla, Aini; Caska, Caska; Suarman, Suarman (Journal of Educational Sciences, 2023)
This research aims to analyze the influence of the use of social media through learning motivation on increasing the learning achievement of Daarun Nahdhah Islamic Boarding School students. The research approach used is quantitative descriptive with data collection techniques using questionnaires and documentation. Sampling used a saturated sample, where all members of the population were used as samples with a total of 90 students who did not live in the dormitory. The data analysis used in the research is Partial Least Square (PLS). The research results show that the use of social media has a direct and indirect effect on student learning achievement. This means that the better the use of social media which is used in a positive direction, the better and better learning achievement will be and the use of social media which is used in a positive direction will increase learning motivation so that student learning achievement will increase.